Зеленые цепочки: повесть / Герман Матвеев - Матвеев Герман Иванович (Школьная библиотека, 2018)
Экземпляры: БС (20200122) / Инвентарный номер: РТШ54886 / Цена: / Сис.шифр: 84(2) / Авт.знак: М 33 / ГРНТИ: 17.82.31 / ББК: 84(2=411.2)6-4